Challenges faced by Turkish students adjusting to multicultural environment in the International Islamic University Malaysia (IIUM) - Togan Nezihat, Sena; Eid, Iyad Muhammad (IIUM Press, 2022)
Even though studying abroad is a very popular phenomenon among students, international students still face challenges in their host country. These adjustments are primarily related to psychological, sociocultural and academic challenges. The purpose of this paper is to investigate the psychological, sociocultural and academic difficulties encountered by Turkish students as they adjust to the new and multicultural environment of International Islamic University Malaysia (IIUM). This study also aims to examine the relationship between the language and academic achievements of Turkish students. This study relies heavily on the qualitative research method, and data from seven Turkish respondents were gathered through in-depth interviews. The interviews were conducted via online platforms and recorded. The interview questions were based on the difficulties they encountered in the host country and the new multicultural environment. Furthermore, the questions were intended to elicit information about the difficulties that Turkish students face at IIUM. The data were analysed with a thematical analysis technique. According to the findings of this study, Turkish students face psychological, sociocultural and academic challenges at IIUM. These challenges are linked to psychological wellbeing, homesickness, loneliness, adapting to a new environment, cuisine, weather and learning a new language. The main themes of this paper are these modifications. The findings of this study will assist future Turkish students in making admissions decisions as well as guide university administration in assisting and managing current and future Turkish students.